Simulation of renewable energy source integration in a smart energy grid using MATLAB/Simulink - Edward Ofoegbu; Harsh Nitin Raichura (Next Energy)
The transformation of the power grid from traditional methods into smart grids for the generation, transmission, distribution, and utilization of electric energy reduces the dependency on fossil fuels, thus taking a step towards environmental sustainability. This research paper simulates a smart grid's behavior when integrated with a renewable energy source. The grid network topology of a power system was modeled and simulated in MATLAB/SIMULINK, where the model consisted of renewable energy resources (RER’s) having a series of solar panels, redundant power generating stations, a transmission infrastructure, and a power utilization section for 3-phase high voltage industrial load and low voltage domestic load, respectively. The results of the study showed that there is power loss and signal distortion in the output voltage when multiple generators are integrated. These harmonics can be easily filtered out when the integration is done between the generator and a renewable energy resource (RER) using properly designed Resistor-Inductor-capacitor filters and booster circuits. The results further demonstrated that when integration was accomplished between the generator and the RERs, a stable output voltage of 0.6e4V was obtained, given a generator capacity of 6600 V. The industrial and domestic load also showed minimal instability by maintaining an output of 1100/440V, respectively, before and after integration. The study also showed that RERs can be used to support the power supply to the grid to maintain its supply voltage and the overall stability of the system. However, RERs cannot withstand supplying a power grid on their own.